Wound Healing Effectivity of Ageratum conyzoides L. Leaf Ethanolic Extract (Purple Flower Type), Centella asiatica (L.) Urban Leaf Ethanolic Extract, and Astaxanthin Combination Gel Preparation in Diabetic Animal Model - Sarah Sahila; Hendy Suhendy; Yedy Purwandi Sukmawan (Sanata Dharma University, 2023)
The diabetic wounds are one of the global burden diseases. In our previous study, Ageratum conyzoides L. leaf ethanolic extract (purple flower type) 10%, Centella asiatica (L.) Urban leaf ethanolic extract 5%, and astaxanthin 0.1% combination gel preparation showed remarkable wound healing effectivity. However, this wound healing effectivity in the diabetic condition is still unknown. There were three groups used, namely negative group (placebo/gel base), positive group (oxoferin/tetrachlorodecaoxide), and test group (Ageratum conyzoides L. leaf ethanolic extract (purple flower type) 10%, Centella asiatica (L.) Urban leaf ethanolic extract 5%, and astaxanthin 0.1%). Each group consisted of three male Wistar rats. We conducted diabetes induction with alloxan (175 mg/Kg BW i.p) and followed by an incision 1.5 cm on the back. All of these groups were given treatment once daily and monitored for 14 days. The results of the study showed the test group indicated significantly better effectivity than positive and negative groups (p0.05). The percentages of the wound healing effectivity of the test, positive and negative groups were 62.74%, 51.77%, and 41.65%, respectively. Ageratum conyzoides L. leaf ethanolic extract (purple flower type) 10%, Centella asiatica (L.) Urban leaf ethanolic extract 5%, and astaxanthin 0.1% combination gel preparation has excellent potential to be developed as a commercial product to treat diabetic wound conditions..